Esthetic Crown Lengthening and Minimally Invasive Laminate Veneers to Resolve Altered Passive Eruption - Cimara Fortes Ferreira; Edival Barreto Magalhães; Barbara Zini (Hindawi Limited, 2024)
Background. Altered passive eruption (APE) in the esthetic zone can be an esthetic concern to the patient. To restore adequate crown dimensions, crown lengthening procedures may be necessary. Methods. The present case is a report of a patient with an unsatisfied smile due to a complaint of short clinical crowns. The periodontal diagnosis was APE and deviated maxillary anterior midline. A mock-up was made to assist the provider in evaluating the patient's esthetic concerns and acceptance of the proposed treatment plan. Results. Esthetic crown lengthening and ultrathin ceramic laminate veneers were used to treat an APE type I subdivision B, resulting in a gingival display reduction and in final PES/WES scores of 10. Conclusion. The use of periodontal plastic surgery in conjunction with ultrathin ceramic laminate veneers was mandatory to restore an unesthetic smile. The proposed treatment reduced the gingival display significantly and increased the crown height to length proportions reaching an esthetic smile and patient satisfaction.